2017
DOI: 10.1084/jem.20161093
|View full text |Cite
|
Sign up to set email alerts
|

Gene silencing and a novel monoallelic expression pattern in distinct CD177 neutrophil subsets

Abstract: CD177 presents antigens in allo- and autoimmune diseases on the neutrophil surface. Eulenberg-Gustavus et al. show that epigenetic silencing causes CD177negative neutrophils, whereas a novel pattern of monoallelic CD177 expression results in a variable percentage of CD177positive neutrophils in bimodal individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 55 publications
0
39
0
Order By: Relevance
“…Epigenetic mechanisms control the CD177 allelesilencing process and one of two CD177 alleles is silenced during neutrophil differentiation, which may cause monoallelic HNA-2 expression in mature neutrophils. 19 In neutrophils from 787A-1291G/787A-1291A (AG/AA) heterozygous donors, neutrophils epigenetically silenced for HNA-2 expression on both chromosomes will appear as the HNA-2-negative population. Since the 787A-1291A (AA) haplotype allele results in much lower HNA-2 expression than 787A-1291G (AG) allele (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic mechanisms control the CD177 allelesilencing process and one of two CD177 alleles is silenced during neutrophil differentiation, which may cause monoallelic HNA-2 expression in mature neutrophils. 19 In neutrophils from 787A-1291G/787A-1291A (AG/AA) heterozygous donors, neutrophils epigenetically silenced for HNA-2 expression on both chromosomes will appear as the HNA-2-negative population. Since the 787A-1291A (AA) haplotype allele results in much lower HNA-2 expression than 787A-1291G (AG) allele (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Humans Several publications have reported that, in healthy individuals, 45-65% of circulating neutrophils are CD177 + [5,6,8,14], with variability of CD177 expression reflecting control by epigenetic mechanisms [15] (Figure 1). CD177 (also known as human neutrophil antigen NB1) is a glycoprotein Neutrophils are the primary responders to infections and tissue damage, but a growing body of evidence suggests that distinct subpopulations of these cells are immunoregulatory and are associated with cancer and other inflammatory diseases.…”
Section: Neutrophil Diversity and Heterogeneity Under Homeostatic Conmentioning
confidence: 99%
“…A dose effect of the wild-type CD177*787A or heterozygosity for both *787A and *787T has been correlated with the proportion of HNA-2-positive neutrophils [10,59]. Recently, gene silencing and a novel monoallelic expression pattern caused by disparate CpG and histone methylation have been described as basis for distinct neutrophil subsets thus introducing epigenetic mechanisms [70]. …”
Section: Hna-2mentioning
confidence: 99%